Prevalence of anti–Leptospira spp. antibodies among donkeys in the semi-arid northeastern region of Brazil (Research, Society and Development, 2022)
Leptospirosis is a zoonotic disease that causes financial and significant problems for herds. The objective was to define a prevalence of Leptospira spp. in serovar samples from 145 stray donkeys from the Brazilian semiarid region using the microscopic agglutination test (MAT), 24 serovars of Leptospira spp. Of the reactive animals, 34 of 145 (23%) had titers between 100 and 3,200. The serovars identified in the sera with high frequency were Kennewicki and Bratislava. In these animals serovars, Pyrogenes, Tarassovi, Canicola, Guaricura, Icterohaemorrhagiae, Grippotyphosa and Copenhageni were also used, showing animals with a lower rate of positive reactivity. This result indicates that the animals studied may be in contact with serovars Kennewicki and Bratislava, since wild animals, rodents and swine may harbor these serovars. Thus, the lack of adoption of protected sanitary measures may favor the occurrence of infection in the sampled animals, prevailing in the herd studied.